Harnessing public research for innovation in the 21st century : an international assessment of knowledge transfer policies - Arundel, Anthony; Athreye, Suma; Wunsch-Vincent, Sacha (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
"Chapter 1 The Evolving Role of Public R&D and Public Research Institutions in Innovation Suma Athreye and Sacha Wunsch-Vincent1 1.1 The growth in policies to leverage public R&D 1.1.1 Why invest in public R&D? Science has consistently been shown to be a fundamental driver of technological progress and economic growth and a source of innovation to the business sector (Jaffe 1989; Adams 1990; Cohen et al. 2002). Its importance for economic progress has grown due to an increase in the role of knowledge as a driver of competitiveness in global markets and from emerging technologies that have opened up new opportunities for development"--
Includes bibliographical references and index.
Keywords: Research, Industrial -- Economic aspects; Technological innovations -- Economic aspects; Technology transfer; Academic-industrial collaboration; Public-private sector cooperation; Technology -- International cooperation; Intellectual property; LAW / Intellectual Property / General; LAW / Intellectual Property / General